Rumor has it - Mason, Jane B.; Hines-Stephens, Sarah (New York : Scholastic, 2010)
"Audrey Jones wants to be friends with the new girl at school, Mailee, but she can't tell if Mailee feels the same about her. So she decides to starts a slam book to get the scoop. Slam books are against school rules, but with pages to write about everyone in the sixth grade, and a code to see who wrote what, Audrey can find out what Mailee really thinks about her. The book is a huge hit--everyone is excited to write (and read!) about everyone else. But does Audrey really want to know the truth?"--P. [4] of cover.
"A candy apple book."
G5
Keywords: Friendship -- Fiction; Gossip -- Fiction; Middle school students -- Fiction; Friendship -- Juvenile fiction; Gossip -- Juvenile fiction; Middle school students -- Juvenile fiction